2019
DOI: 10.17759/jmfp.2019080408
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ attitude to use of digital technology by young children

Abstract: The article provides a review of studies concerning the parent’s attitude to digital technology utilization of their young children. Data presented show an increase in intensity and a significant decrease in the age at which children start using mobile devices, including smartphones and tablets. It is shown that new technologies significantly change the relationship of children and parents. Variants of parental mediation strategies in the process of using digital technologies are highlighted and described: res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The data, obtained in a sample of children with experience of using media, confirmed that poor play behavior with real toys played a key role in causing screen time tantrums. Thus, play, as a leading activity in preschool age, should be seen as a key to children’s development and learning, but also as a way of setting screen time limits ( Smirnova et al, 2019 ). To our knowledge, this is the first study aimed at the exploring the predictors of screen time tantrums in children.…”
Section: Discussionmentioning
confidence: 99%
“…The data, obtained in a sample of children with experience of using media, confirmed that poor play behavior with real toys played a key role in causing screen time tantrums. Thus, play, as a leading activity in preschool age, should be seen as a key to children’s development and learning, but also as a way of setting screen time limits ( Smirnova et al, 2019 ). To our knowledge, this is the first study aimed at the exploring the predictors of screen time tantrums in children.…”
Section: Discussionmentioning
confidence: 99%
“…In the works of Zinovieva Ludmila Vasilievna and Mokhonko Daria Andreevna on "communication specificity within the "deaf parentshearing children" dyad they give the specifics of the model of family relations which are determined especially of emotional and communicative interaction in the dyad "hearing childdeaf parent". Along with difficulties in accepting the deafness of parents by children, deaf parents, in turn, may face emotional and psychological problems associated with feelings of low value, helplessness, and guilt for the forced need to use the child's auditory abilities for their purposes [9]. First model.…”
Section: Materials and Discussionmentioning
confidence: 99%
“…The hearing children of adolescence show unpleasant attitudes towards deaf parents, expressing this in the form of dominant and manipulative behaviour. The children are ashamed of the deafness of their parents, which prevents them from appearing at school and at parent meetings, insisting on the presence of hearing relatives, in particular grandmothers, who, as a rule, occupy an authoritative position in the family [9].…”
Section: Materials and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart technologies and free access to the Internet have triggered a powerful generational shift not seen before [12]. If even thirty years ago, the boundaries of generations were quite blurred and conditional, that today's Generation Alpha is radically different from previous generations [13].…”
Section: Introductionmentioning
confidence: 99%